Pengaruh Psychological Capital terhadap Work Engagement pada Barista di Kota Bandung - Yasyfa Camilla Pudjiadi; Sita Rositawati (Bandung Conference Series: Psychology Science, 2022)
Abstract. Challenges in the workplace will constantly be there, so that for employees to be engaged at work, needs to be balanced with high resources (Bakker & Demerouti, 2008). Suggestions from the research of Erum et al. (2020) and Chinelato et al. (2019), work engagement can be increased with personal resources, namely psychological capital, because it can be more flexible and adaptive when overcoming challenges and provides a competitive advantage. This research was conducted in the hospitality sector in which this research is still limited (Karatepe & Karadas, 2015), whereas work engagement can provide business benefits and excellent service quality such as customer satisfaction and loyalty, profitability, productivity, and security (Paek et al., 2015). This study aims to empirically examine the effect of psychological capital towards work engagement in the business and service sectors. The subjects of this study is 153 baristas who works at informal coffee shops in Bandung city. Samples are collected using convenience sampling technique. The research method used is quantitative with causality research design using multiple regression technique. Measurement scale using the Psychological Capital Questionnaire (PCQ) from Luthans et al. (2007) and the Utrecht Work Engagement Scale (UWES) from Schaufeli & Bakker (2003). The results of this research shows that there is a positive effect of psychological capital towards work engagement by 33.4% (R Square = .334). The dimension of psychological capital that has the biggest influence on work engagement is optimism (12.4%) and the dimension that has no significant effect is self-efficacy (2%). Abstrak. Tantangan di tempat kerja akan selalu ada, maka agar karyawan dapat engaged terhadap pekerjaannya, perlu diimbangi dengan sumber daya yang tinggi (Bakker & Demerouti, 2008). Saran dari penelitian Erum et al. (2020) dan Chinelato et al. (2019), work engagement dapat ditingkatkan dengan sumber daya pribadi yaitu psychological capital, karena dapat lebih fleksibel dan adaptif ketika mengatasi tantangan, sehingga memberikan keunggulan yang kompetitif. Penelitian ini dilakukan pada bidang pelayanan yang penelitiannya masih terbatas (Karatepe & Karadas, 2015), padahal work engagement dapat memberikan keuntungan bisnis dan kualitas pelayanan yang unggul seperti kepuasan dan loyalitas pelanggan, profitabilitas, produktivitas, dan keamanan (Paek et al., 2015). Penelitian ini bertujuan untuk menguji secara empiris pengaruh psychological capital terhadap work engagement pada bidang bisnis dan pelayanan. Subjek dalam penelitian ini adalah 153 barista yang bekerja di Coffee Shop informal di Kota Bandung. Sampel dikumpulkan menggunakan teknik sampling convenience. Metode penelitian yang digunakan adalah kuantitatif dengan desain penelitian kausalitas menggunakan teknik multiple regression. Skala pengukuran menggunakan alat ukur Psychological Capital Questionnaire (PCQ) dari Luthans et al. (2007) dan Utrecht Work Engagement Scale (UWES) dari Schaufeli & Bakker (2003). Hasil penelitian menunjukkan terdapat pengaruh positif psychological capital terhadap work engagement sebesar 33.4% (R Square = .334). Dimensi psychological capital yang paling besar pengaruhnya terhadap work engagement adalah optimism (12.4%) dan dimensi yang tidak signifikan pengaruhnya adalah self efficacy (2%).